PENERAPAN METODE GRAPHIC RATING SCALE (GRS) DALAM PENILAIAN KINERJA KARYAWAN - Redaksi Tim Jurnal (KILAT, 2017)
Competition increasingly competitive business trigger Muliadana company to be more innovative in improving the quality of the company. One technique used by management companies in improving the quality of human resources is to conduct employee performance appraisal. To the authors try to establish a scoring system using the Graphic Rating Scale (GRS), which is a methodology for assessing the scale of the graph by comparing the individual performance against an absolute standard. The purpose of this valuation method is to minimize the less objective assessment and can determine the development of the employee's performance over several periods. The results of the performance appraisal company can provide feedback to the employees so they can decide the steps taken in making decisions such as: promotion, promotion or class, mutation, degradation as well as training for employees in need.